Cartography of the real estate tsunami: the popular urban movement and the urban-rural links of the real estate boom in Mexico City - Flores, Adrián (2019)
Mexico City is one of the oldest and largest urban concentrations in the world. It constitutes a vastconcentration of labor power and means of production that represents a formidable capacity forextracting profits, and requires a complex management for its control. In recent years the battle forthe metropolis has become more acute and is currently expressed in the expansion of real estatedevelopments, named by popular urban movement as the real estate tsunami. This is the densificationof the urban core from the vertical expansion of the city through the construction of housing towers,but also through the expansion of new transport networks such as MetroBus (Bus Rapid Transport) andthe overlap of controlled access roads, the expansion of shopping centers, the privatization of publicspaces (pocket parks), the elimination of unbuilt spaces, the displacement of the poorest population ofurban centers from violent dispossessions and evictions and its replacement with vertical overcrowdingof a long-term indebted population with the real estate industry. To understand this new phase ofurban expansion, a cartography of this real estate tsunami is carried out, under the assumption thatmaking visible the coordination of business and state strategies of appropriation of urban land, allows tounderstand and fundamentally strengthen the popular urban movements.